Commentary paper: enhancing transformative learning in nursing education through Massive Open Online Courses (MOOCs) - Aung, Khin Thandar; Abdul Razak, Rafiza; Mohamad Nazry, Nor Nazrina (MNNF Publisher, 2023)
Nursing education is a soft-applied discipline. This discipline applies its knowledge to the field of human health. Transformative learning is an educational approach that emphasizes the process of personal and professional development through critical reflection and critical thinking. In nursing education, transformative learning can play a significant role in developing nurses who are able to provide safe and effective care to patients and adapt to the changing healthcare landscape. Massive Open Online Courses (MOOC) have gained popularity as an innovative approach to education. Those who are unable to attend traditional face-to-face classes have access to a quality education through MOOCs, which provide a platform for learners to interact with experts from around the globe. The transformative learning theory has been identified as a key concept that can be used to explain the potential impact of MOOCs on nursing education. This paper will explore the relationship between MOOCs and transformative learning in nursing education and how to enhance transformative learning for nurses.